Financial Performance Analysis of Share Prices in Banking Companies Listed on the Indonesia Stock Exchange 2020-2023 period - Dinda Putri Syafrila; Maya Syaula; Ramadhan Harapan (Outline Journal of Economic Studies, 2025)
This research aims to analyze whether investment decisions, profitability, and capital structure have a positive and significant effect on stock prices in state-owned banking companies listed on the Indonesia Stock Exchange during the 2020–2023 period. The research method used is associative quantitative research with a descriptive approach. The analysis technique used is multiple linear regression analysis to test the simultaneous and partial effects of the independent variables on the dependent variable. The sample consists of four state-owned banking companies, namely Bank Negara Indonesia (BBNI), Bank Rakyat Indonesia (BBRI), Bank Tabungan Negara (BBTN), and Bank Mandiri (BMRI), with data collected from quarterly financial reports over the four-year period. The results of the regression analysis show that investment decisions, profitability, and capital structure each have a positive and significant partial effect on stock prices. Furthermore, the simultaneous testing results also confirm that the three financial performance indicators together significantly influence stock price movements. These findings indicate that improved financial decision-making in these areas contributes to enhancing investor confidence, which in turn drives stock prices upward. Therefore, companies need to maintain and strengthen their financial strategies to ensure long-term value creation for shareholders in the capital market.